Identification of Phytosphingosine-Based 1-O-Acylceramide in Human Stratum Corneum and Investigation of Its Role in Skin Barrier - Bae-Gon Kang; Hyun Kyung Choi; Kwang-Hyeon Liu; Sung Kyu Hong; Jin Wook Kim; Eun Ok Lee; Chang Seo Park (Cosmetics)
Phytosphingosine-based 1-O-acylceramide (CerENP) from the human stratum corneum has not been reported on. High-resolution mass spectrometry was used to identify CerENP from skin samples. A vehicle-controlled human study was performed to investigate the physiological interaction between ceramide NP (CerNP) and CerENP with respect to skin hydration, cohesion, and TEWL, all of which were measured. Twenty volunteers were treated with test creams containing CerENP together with CerNP, which significantly improved skin barrier parameters after four weeks of application: 1. Skin hydration was increased by 26% compared to when CerNP was used alone, and moisture retention was better than it was with the CerNP control. 2. Stratum corneum (SC) cohesion was strengthened significantly only when using the test cream formulated with CerENP. The results suggested the boosting effects of CerENP on the skin barrier functions exerted by CerNP since only a small amount is required, as low as one-tenth of CerNP. This is the first report on the identification of CerENP in the human SC and its skin barrier activities in human skin. In conclusion, the combinatorial use of CerENP and CerNP at an appropriate relative ratio could be a new normal in developing an ideal moisturizer for dry and atopic skin.